A review on environmental impacts from aviation sector in terms of life cycle assessment. (2nd October 2020) - Calisir, Duran; Ekici, Selcuk; Midilli, Adnan; Karakoc, Tahir Hikmet
The main objective of this paper is, in terms of LCA (life cycle assessment), to compile and discuss, environmental impacts of aircraft, gas turbine engine and components, and maintenance process and operations in the aviation sector. The study reveals in detail LCA implementations on aircraft and related products and processes and unmanned aerial vehicles, as well as LCA's historical development, purpose, scope and method classification. The value of this study lies in the review of LCA studies in the aviation industry to emphasise the importance and feasibility of sustainable development in the aviation industry. This motivation behind the study shows to practitioners and researchers how the LCA approach can be applied in aviation through studies in the literature. Thus, this paper will contribute to scientists, researchers, designers, manufacturers and policymakers on the aviation industry for better understanding the environmental impacts from aviation sector in terms of life cycle assessment.